ETIKA BISNIS DAN ETIKA PROFESI AKUNTAN - Widaryanti . (STIE Pelita Nusantara Semarang, 2007)
Accountant ethics have discused in peoples. Ethics consists of moral principles and standard of conduct. In general use the word ethics relates to the philosophy of human conduct and principles of human morality and duty. Professional ethics include standards of behaviour for a professionalperson that are designed for both practical and idealistic purposes. The deliquency of accountant profesional ethics codes at company have a lot of number, so it is need more power to obey that codes. If there is an regulation and punishment, the profesional ethics will not breached. Besidethat, if all of wrong behaviours is going on, so far, it will be a habit. This wrong norm will be a culture. Because of that, some one have breach the rule, he must get the punishment to learn of what it education environment. Accounting educations have big influences to ethics of accounting behaviour, so it’s need to know about what accountant learning (student university) to ethics problems,in this term is business ethics and accountant profesional ethics which will they faces